Species Diversity of Seagrass in Marsegu Island, West Seram Regency, Maluku Province - Leimena, Handy E P (Jurnal Laot Ilmu Kelautan, 2025)
Seagrass is one of the most important marine ecosystems, providing a wide range of ecosystem services that support coastal and marine life. The presence of seagrass in coastal areas plays a crucial role as a provider of ecosystem goods and services, serving as habitat and breeding grounds for various marine organisms, and offering relatively higher fishery resources compared to mangrove and coral reef ecosystems. This study aims to determine the species diversity of seagrass in Marsegu Island, West Seram Regency. The research was conducted through several systematic stages, beginning with a preliminary site survey using the linear-quadrat transect method to determine the number of transects required. Subsequently, research equipment and materials were prepared. The next stage involved the establishment of transects and observation plots—thirteen transects were positioned perpendicular to the shoreline at 25 m intervals, and ten observation plots (1 × 1 m) were placed alternately along each transect at 7 m intervals. Seagrass samples were collected during low tide using the same linear-quadrat transect method. The collected samples were then scientifically identified at the Ecology Laboratory, Department of Biology, Faculty of Science and Technology, Pattimura University. The results revealed that three seagrass species were found along the coast of Marsegu Island, namely Thalassia hemprichii, Halophila sp., and Enhalus acoroides, with a total of 3,077 individual plants recorded. Ecological index analysis indicated that seagrass diversity in this area was relatively low, although no single species showed significant dominance within the community. These findings suggest that the seagrass community structure in Marsegu Island remains relatively simple yet ecologically stable, providing essential baseline data for conservation and coastal ecosystem management efforts in the region.